2021
DOI: 10.3390/jmse9020106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impeller Gap Drainage Width on the Performance of Low Specific Speed Centrifugal Pump

Abstract: The centrifugal pump is one of the most important pieces of energy-consuming equipment in various hydraulic engineering applications. This paper takes a low specific speed centrifugal pump as the research object. Based on the research method combining numerical calculation and experimental verification, the influence of the gap drainage structure on the performance of the low specific speed centrifugal pump and its internal flow field distribution were investigated. The flow field inside the low specific speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The general performance and physical limitations of LSS pumps have been investigated by Kurokawa [6] and Olimstad [7]. Special design has also been proposed by Klas [8,9] where thick trailing edge replaced classic blading, or more recently by Wei [10] and Yang [11] who tested slit impeller blades on a pump with a specific speed n q = 5.7. Nonetheless, the most common solutions for LSS pumps is the addition of splitter blades to the impeller, to raise the pressure developed by the impeller as extensively studied in references [12][13][14][15][16][17], where generally variations of a splitter blade position in the impeller passage is studied for pump optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The general performance and physical limitations of LSS pumps have been investigated by Kurokawa [6] and Olimstad [7]. Special design has also been proposed by Klas [8,9] where thick trailing edge replaced classic blading, or more recently by Wei [10] and Yang [11] who tested slit impeller blades on a pump with a specific speed n q = 5.7. Nonetheless, the most common solutions for LSS pumps is the addition of splitter blades to the impeller, to raise the pressure developed by the impeller as extensively studied in references [12][13][14][15][16][17], where generally variations of a splitter blade position in the impeller passage is studied for pump optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In the turbulent transport equation, the unsteady term is a second-order difference, and the convection term is an upwind difference. Considering the factors such as calculation cost and calculation accuracy, the SST k-ω model is finally selected as the turbulence model (Han et al, 2021;Wei et al, 2021).…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…Ignoring smaller magnitudes, simplify equation (21) to From equation (22c), we can get the following result: the pressure p of the fuid boundary layer does not change along the y direction. Tis indicates that the fuid disturbance is caused by a pressure change in the x-axis direction: during fow channel difusion, there is a negative pressure gradient in the x-axis direction, that is, zp/zx < 0 in equation (22b).…”
Section: Meshmentioning
confidence: 99%
“…Currently, some scholars have studied the relationship between the shape of the slit vane and the performance of centrifugal pumps by using orthogonal tests, but they are not very comprehensive [19,20]. Zhang et al and Wei et al investigated the efect of slot width on drainage performance [21,22]. Te study found that slot drainage will reduce the head, but it will increase its hydraulic efciency.…”
Section: Introductionmentioning
confidence: 99%